Global research trends on artificial intelligence in psychological interventions for stroke survivors: a bibliometric and visualized analysis (2000–2024) - Li, Yaoyao; Soh, Kim Lam; Sun, Fengna; Wei, Lili; Saidi, Hasni Idayu; Soh, Kim Geok (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to conduct a bibliometric analysis of research literature on AI-assisted psychological interventions for stroke survivors published from 2000 to 2024, using CiteSpace and VOSviewer to examine research collaboration networks, knowledge structures, and developmental trends.MethodsLiterature data was sourced from the Web of Science Core Collection database (WoSCC). A total of 450 relevant articles, published between 1 January 2000 and 31 October 2024, were included. CiteSpace and VOSviewer were employed to analyze the literature from dimensions including authorship, country of origin, institutions, journals, references, and keywords.ResultsAnnual publication output has steadily increased, reaching a peak in 2022 (72 articles), followed by 68 articles in 2023 and 69 articles in 2024. Calabro Rocco Salvatore emerged as the most productive author (9 publications). The United States led in research output (87 articles) and centrality (0.51), with McGill University being the leading institution (10 articles). “Journal of NeuroEngineering and Rehabilitation” was the most productive journal (24 articles), while “Stroke” was the most co-cited journal (347 times). Recent research trends focused on ischemic stroke (strength = 3.09), anxiety (strength = 2.72), cognitive impairment (strength = 2.67), and meta-analysis (strength = 2.58), reflecting a shift toward integrated assessment and intervention strategies.ConclusionThis bibliometric analysis reveals a significant evolution in research on AI-assisted psychological interventions for stroke survivors, shifting from single technology applications to integrated services encompassing assessment, monitoring and intervention. Future research should continue to strengthen empirical studies while enhancing interdisciplinary collaboration to improve the quality of psychological healthcare services.